Practical Skills and Practical Wisdom in Virtue. Issue 3 (2nd July 2016) - Stichter, Matt
ABSTRACT: This paper challenges a frequent objection to conceptualizing virtues as skills, which is that skills are merely capacities to act well, while virtues additionally require being properly motivated to act well. I discuss several cases that purport to show the supposed motivational difference by drawing our attention to the differing intuitions we have about virtues and skills. However, this putative difference between virtue and skill disappears when we switch our focus in the skill examples from the performance to the performer. The ends of a practice can be used to judge not only the skilfulness of a performance, but also the motivational commitment of the performer. Being virtuous requires both acting well and being properly motivated to do so, which can be captured by viewing virtues as the moral subset of skills. In claiming this, though, I resist the idea that there is no element in virtue that is not found in other skills. Virtue requires being practically wise about how practices fit into a conception of the good life, but other skills do not. I further argue that this difference doesn't undermine the 'virtue as skill' thesis, as it's the connection between virtues and morality that requires practical wisdom.